The potential of light fidelity in smart home automation - Aydin, Hakan; Aydın, Gülsüm Zeynep Gürkaş; Aydın, Muhammed Ali (Bulletin of Electrical Engineering and Informatics, 2024)
Light fidelity (Li-Fi) is a pioneering optical wireless communication (OWC) technology that utilizes visible light for wireless data transmission. Since its inception in a TED global talk by Professor Harald Haas in 2011, Li-Fi has captured significant attention in the research community. Smart home automation systems (SHAs) leverage internet of things (IoT) technology to remotely manage and automate various home devices and systems. Li-Fi technology has the potential to enable remote control of devices such as lighting, air conditioning, music systems, security cameras, and door locks within SHAs. This study presents Li-Fi-IoT, a Li-Fi-based system designed for efficient and secure IoT device management in SHAs. A series of experiments demonstrates the system's potential in IoT device control using Li-Fi technology. The research findings highlight the substantial improvement in data transfer speed, energy efficiency, and data security that Li-Fi technology can bring to SHAs.